THE ROLE OF THE FAMILY IN FULFILLING THE SPIRITUAL NEEDS OF THE ELDERLY IN RT 021/ RW 009 SAKO VILLAGE PALEMBANG CITY - Ira Tri Astuti; Mega Nurrizalia (IKIP Siliwangi Bandung, 2023)
The purpose of this study is to describe the role of the family in meeting the spiritual needs of the elderly in RT.021 RW.009, Sako Village, Palembang City. The type of research used is descriptive with a qualitative approach. Data collection was done by interview, observation and documentation. The subjects of this study were eight people, namely four elderly and four elderly families. The results showed that the role of the family in fulfilling the spiritual needs of the elderly had not been implemented properly. The role of the family in meeting the spiritual needs of the elderly, among others, is a relationship with God, a relationship with oneself, a relationship with others and a relationship with nature. The role of the family in the relationship with God has not been carried out properly, the elderly family pays less attention to and reminds the elderly to worship. However, the elderly already have their own awareness to increase their deeds of worship as provisions in the afterlife. Relationships with oneself are like helping the elderly in finding their purpose in life and helping the elderly solve their problems. Relationships with other people such as providing information and taking trips. Relationships with nature such as facilitating the elderly to keep the environment clean and facilitating the elderly in maintaining the coolness of the environment by farming. To support the spiritual activities of the elderly, the family provides care in the form of spiritual care, physical care, psychological care and social care and it is hoped that the Sako Village will further improve spiritual facilities for the elderly.